2011
DOI: 10.1590/s1982-56762011000100004
|View full text |Cite
|
Sign up to set email alerts
|

Controle de Fusarium oxysporum f.sp. phaseoli in vitro e em sementes, e promoção do crescimento inicial do feijoeiro comum por Trichoderma harzianum

Abstract: RESUMOEste trabalho objetivou avaliar seis isolados de Trichoderma harzianum no controle de Fusarium oxysporum f.sp. phaseoli em sementes, e seu efeito no crescimento inicial do feijoeiro comum. Os isolados foram inicialmente confrontados in vitro com o patógeno em testes de cultura pareada e antibiose a 25ºC. Sementes sadias e artificialmente infectadas pelo patógeno foram microbiolizadas com 2 mL de suspensões dos antagonistas (2,5 x 10 8 conídios mL -1 ) para cada 100 g de sementes, em rolo de papel germtes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0
24

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 15 publications
2
28
0
24
Order By: Relevance
“…However, the general means of the treatments showed significant reduction in germination after seeds were contaminated by S. sclerotiorum. In addition, seed treatments with 2 mL of suspension at 2.5x10 8 conidia mL -1 of T. harzianum per 100 g of seeds did not cause any toxicity to germination (Carvalho et al, 2011).…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…However, the general means of the treatments showed significant reduction in germination after seeds were contaminated by S. sclerotiorum. In addition, seed treatments with 2 mL of suspension at 2.5x10 8 conidia mL -1 of T. harzianum per 100 g of seeds did not cause any toxicity to germination (Carvalho et al, 2011).…”
Section: Resultsmentioning
confidence: 83%
“…A possible explanation for the antagonism of these two isolates against the pathogen, in contrast to the other Trichoderma isolates, could be the performance of biological control mechanisms, including hyperparasitism, which can vary between species and among isolates of the same species (Martins-Corder & Melo, 1998;Louzada et al, 2009). Carvalho et al (2011) reported lower efficacy in the biocontrol of F. oxysporum f. sp. phaseoli in seeds, with Carboxin+Thiram responsible for 73% reduction in the pathogen, while the biological treatment provided decreases of 35 to 51%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Após esse período, um disco de meio de cultura BDA, também com 12 mm de diâmetro, contendo micélio de Trichoderma, foi transferido para a posição oposta ao disco de micélio de Fusarium nas placas de Petri (a 0,5 cm da borda da placa). As placas foram incubadas durante 7 dias a 25 ± 2 °C com fotoperíodo de 12 h (CARVALHO et al, 2011). Decorrido esse tempo, as placas foram avaliadas de acordo com o critério de Bell, Wells e Markham (1982), baseado em uma escala de notas variando Detecção de Fusarium spp.…”
Section: Methodsunclassified
“…em soja sob plantio direto de 1 a 5, na qual em 1 -Trichoderma cresce e ocupa toda a placa; 2 -Trichoderma cresce e ocupa uma parte do patógeno (Fusarium) (2/3 da placa); 3 -Trichoderma e Fusarium crescem até a metade da placa (nenhum domina o outro); 4 -Fusarium cresce e ocupa uma parte do Trichoderma (2/3 da placa); e em 5 -Fusarium cresce e ocupa toda a placa de Petri. Em seguida, as notas do antagonista foram agrupadas em classes (CARVALHO et al, 2011).…”
Section: Methodsunclassified